Konsep Pendidikan Spiritual Imam Al-Ghazali dan Relevansinya terhadap Pengembangan Kurikulum Pendidikan Islam - Syah Putra, Kurniawan (Jurnal Ilmiah Guru Madrasah, 2024)
Imam Al-Ghazali is one of the great figures in Islamic thought who paid close attention to the aspect of spiritual education. According to Al-Ghazali, the concept of spiritual education is not only oriented towards intellectual aspects, but also towards the moral and spiritual development of students. This article aims to examine the concept of spiritual education in Al-Ghazali's thought and relate it to the development of the current Islamic education curriculum. The method used is a literature review with a descriptive qualitative approach. The findings reveal that spiritual education in Al-Ghazali's perspective encompasses tazkiyatun nafs (purification of the soul), takhalli (emptying oneself of undesirable traits), and tahalli (filling oneself with virtuous traits). The relevance of Al-Ghazali's thought can serve as a foundation for curriculum development that emphasises the formation of character, ethics, and spirituality among students